Forest-Limit (Betula pubescens ssp. czerepanovii) Performance in the Context of Gentle Modern Climate Warming - Kullman, Leif (European Journal of Applied Sciences, 2022)
In the context of post-Little Ice Age climate change, regional forest-limit (strictly defined) adjustment was studied over the period 1915 to 1975. The study comprised nearly 200 sites, in the form of systematically distributed belt transects. Forest-limit positions (m a.s.l.) were reconstructed for the years around 1915 and compared to the situation about 1975. During that interval, summer temperatures (June-August) increased by 1.2 °C. Concurrently, elevational upshifts were ubiquitous, site specific and rather modest; c. 17 altitudinal meter rise over a period of about 60 years. This is far less than expected for the climate change alone and indicates a pronounced disequilibrium situation. In comparison, the treeline in the same area, i.e. the uppermost > 2 m tall birches, advanced by average c. 35 m. Thus, it appears that the treeline is a more sensitive biomonitor than the forest-limit. Therefore, the forest-limit should be primarily focused in the context of environmental monitoring. Given that the current relatively warm climate phase continues, the subalpine birch forest belt may eventually recede and give way to a subalpine pine belt. The obtained modest forest-limit advancement is so small that flourishing model simulations of extensive birch forest expansion over most of the current alpine tundra, appear as large and unfounded exaggerations. The alpine tundra of the Scandes, with its characteristic biodiversity, is likely to prevail for a foreseeable future.